The First Female Dry Immersion (NAIAD-2020): Design and Specifics of a 3-Day Study - Tomilovskaya, Elena; Amirova, Liubov; Nosikova, Inna; Rukavishnikov, Ilya; Chernogorov, Roman; Lebedeva, Svetlana; Saveko, Alina; Ermakov, Ivan; Ponomarev, Ivan; Zelenskaya, Inna; Shigueva, Tatiana; Shishkin, Nikita; et al. (Frontiers in Physiology, 2021)
This article describes procedures and some results of the first study of females undergoing 3-day Dry Immersion. The experiment “NAIAD-2020” was carried out at the Institute of Biomedical Problems (Moscow, Russia) with the participation of six healthy women volunteers (age 30.17 ± 5.5 years, height 1.66 ± 0.1 m, weight 62.05 ± 8.4 kg, BMI 22.39 ± 2.2 kg/m2) with a natural menstrual cycle. During the study, a standard protocol was used, the same as for men, with a minimum period of time spent outside the immersion bath. Before, during and after Immersion, 22 experiments were carried out aimed at studying the neurophysiological, functional, metabolic and psychophysiological functions of the body, the results of which will be presented in future publications. The total time outside the bath for women did not exceed that for men. Systolic and diastolic pressure did not significantly change during the immersion. In the first 24 h after the end of the immersion, heart rate was significantly higher than the background values [F(4,20) = 14.67; P < 0.0001]. Changes in body temperature and water balance were consistent with the patterns found in men. No significant changes in height and weight were found during immersion. All women reported general discomfort and pain in the abdomen and back. The results of this study did not find significant risks to women’s health and showed the feasibility of using this model of the effects of space flight in women of reproductive age.